ProjecTables: Augmented CNC tools for sustainable creative practices. (September 2018) - Rasmussen, Troels A; Merritt, Timothy
Computer numerical control (CNC) cutting machines have become essential tools for designers and architects enabling rapid prototyping, model building, and production of high-quality components. Designers often cut from new materials, discarding the irregularly shaped remains. We introduce ProjecTables, a visual augmented reality system for interactive packing of model parts onto sheet materials. ProjecTables enables designers to (re)use scrap materials for computer numerical control cutting that would have been previously thrown away, at the same time supporting esthetic choices related to wood grain, avoiding surface blemishes, and other relevant material properties. We conducted evaluations of ProjecTables with design students from Aarhus School of Architecture, demonstrating that participants could quickly and easily place and orient model parts reducing material waste. Contextual interviews and ideation sessions led to a deeper understanding of current work practices and sustainability issues with computer numerical control cutting machines and identified useful features for interactive packing to reduce waste while supporting esthetic concerns for exhibition quality design projects.